(project-i(s)les). - Baudrillard, Jean; Delafortrie, Lieven; Eco, Umberto; González-Sancho, Eva; Kalakowski, Leszek; Nabakov, Vladimir; Vinci, Leonardo da; Warhol, Andy; St.-Michelgebouw Brussel; Hogeschool Sint-Lukas Brussel (2001)
Deze catalogus wordt uitgegeven ter gelegenheid van het afstudeerproject project-i(s)les door de vzw Artquake 2001.
Boudewijns, Jan(us) ; De Buisseret, Marie-Pierre ; de Bus, Steven ; de Clerck, Mario ; de Maeyer, Kathleen ; de Smet, Annelies ; de Wilde, Frederik ; Dumont, Johan ; Goossens, Inge ; Hermans, Leen ; Laute, Vincent ; Marit, Liesbeth ; Matthijs, Elke ; Murphenko, Michael ; Muylle, Brice ; Nauwynck, Dries ; Oosterlinck, Dimitri ; Rutten, Andries ; Sanders, Mira ; Sanders, Tina ; Schols, Tom ; Timmermans, Ante ; Vandromme, Jan ; Vervaet, Filip
Engels
Frans
Nederlands
project-i(s)les, St.-Michelgebouw Brussel / Hogeschool Sint-Lukas Brussel, 15.06 - 02.07.2001
boek